2015
DOI: 10.3390/biom5043193
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Apoptosis: Friends or Foes?

Abstract: Alcohol abuse causes 79,000 deaths stemming from severe organ damage in the United States every year. Clinical manifestations of long-term alcohol abuse on the cardiac muscle include defective contractility with the development of dilated cardiomyopathy and low-output heart failure; which has poor prognosis with less than 25% survival for more than three years. In contrast, low alcohol consumption has been associated with reduced risk of cardiovascular disease, however the mechanism of this phenomenon remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 31 publications
(54 reference statements)
0
22
0
5
Order By: Relevance
“…During the alcohol exposure, the cellular signaling pathway, which regulates cell proliferation and survival, is inhibited. Previous reports showed that alcohol suppressed the PI3K/AKT signaling pathway in liver cells [52,53]. However, it is still unclear to determine the level of inner ear alcohol content by alcohol exposure in BAC of alcohol content.…”
Section: Discussionmentioning
confidence: 97%
“…During the alcohol exposure, the cellular signaling pathway, which regulates cell proliferation and survival, is inhibited. Previous reports showed that alcohol suppressed the PI3K/AKT signaling pathway in liver cells [52,53]. However, it is still unclear to determine the level of inner ear alcohol content by alcohol exposure in BAC of alcohol content.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, alcohol increased caspase 3 staining (4–5 months liquid diet) in male Wistar rats (99) and caspase 3 protein and activity in alcohol-fed male mice (15, 57). Acutely, cleaved caspase-3 was also increased by alcohol (3g/kg/day, 3 days) in male mice (95).…”
Section: Apoptosismentioning
confidence: 99%
“…Myocyte loss by necrosis or apoptosis is a relevant mechanism in cardiac dysfunction and is present in major heart diseases [70]. High-dose alcohol consumption has clearly shown to increase cardiac apoptosis pathways in animal [23] and human studies [24]. Thus, pro-apoptotic mechanisms are activated in alcoholic patients without heart damage.…”
Section: Strategies To Decrease Factors Inducing Heart Damagementioning
confidence: 99%
“…Thus, pro-apoptotic mechanisms are activated in alcoholic patients without heart damage. Chronic alcoholic subjects with structural heart damage showed higher apoptotic indexes in deoxyribonucleotidyl transferase-mediated dUTP-biotin nick end-labeling, Bax, and Bcl-2 assays as compared with control subjects [23,24]. Since the control of myocyte apoptosis is a key factor in alcohol-induced heart damage [9], the most relevant strategies to control cardiac hypertrophy and myocyte loss include the following.…”
Section: Strategies To Decrease Factors Inducing Heart Damagementioning
confidence: 99%